Spiritual Care for Non-Communicative Patients : a Handbook. - Golding, Linda S. (Jessica Kingsley Publishers, 2019)
This book enables chaplains to deliver vital spiritual care to non-responsive patients and their families. With exercises, worksheets and case studies, it demonstrates how chaplains can develop the confidence and skills needed to engage with patients in meaningful ways, while affirming their personhood and bringing comfort to their loved ones.